A freestanding cathode with bimetallic MOF-based composites anchored on N-doped porous carbon nanofibers for lithium-oxygen batteries. (20th November 2021) - Zhang, Xiuling; Peng, Lichong; Zhai, Zhenyu; Fong, Hao; Liu, Yuanfeng; Li, Congju
Abstract: Simultaneously achieving both bifunctional catalysts and flexible self-supported electrodes are urgently in demand to satisfy rechargeable lithium-oxygen (Li-O2 ) batteries, particularly for wearable devices. Herein, we propose a novel strategy embracing electrospinning and hot-pressing to develop Co-based composites embedded in porous nitrogen-rich carbon nanofibers (ZnCo-NC/NCF) as a freestanding cathode for Li-O2 batteries. The fabricated electrode is obtained through pyrolysis of bimetallic (ZnCo) zeolitic imidazolate frameworks/polyacrylonitrile (PAN) nanofibers (BMZIF/PAN). Benefiting from outstanding mechanical strength of electrospun carbon matrix and abundant porosity originated from decomposition of ZIFs as well as fully exposed Co-Nx active sites, the achieved cathode is capable of excellent flexibility, high specific surface area, great conductivity and good catalytic behaviors towards both oxygen reduction/evolution reactions. Consequently, the corresponding Li-O2 batteries exhibit remarkably decreased voltage gap (0.49 V), high specific areal capacity (9.52 mAh cm −2 ) and long-term cycling capability (around 42 cycles under a curtailing capacity of 0.25 at 0.04 mA cm −2 ). Besides, the evolution of the morphology and electrochemical impedance spectroscopy at various reaction states are further investigated, which confirms that ZnCo-NC /NCF cathode enables formation and decomposition of lithium peroxide during charge-discharge period.